Pelatihan Analisis Data Non Parametrik Dengan Aplikasi RStudio Bagi Mahasiswa Prodi Bimbingan Konseling - Muhammad Taqwa; Karman Lanani (LPPI UMN AL WASHLIYAH, 2024)
Data analysis is an important part of the research process with parametric and non-parametric statistical tests. However, many students still fail to process research data, especially non-parametric statistical tests, including guidance and counselling study program student of STKIP Andi Matappa. This community service activity aims to increase students' ability to understand the processing of non-parametric statistical tests for research. This service is carried out as part of the solution to the problems they face in completing their studies where there are still many students who are still confused about processing the data from their research and interpreting the results of the processed data into conclusions and discussions in their research. The target of this activity is STKIP final student Andi Matappa, who consists of the guidance and counselling study program, where each study program is represented by 20 students so the total number of participants in this training is 12 people. This training method uses a simulation method. The results of the service show an increase in student's knowledge about processing data with non-parametric statistical tests with RStudio software.